A consumer perception trust model for e-commerce websitea - Che Hussin, Ab. Razak (Faculty of Computer Science and Information System, 2009)
Trust is a vital element to the success of e-commerce. The research on the concept of trust has emerged rapidly due to the need of understanding it in order to improve current and future e-commerce implementation. The lack of consumer trust is one of the focused issues today as the world moves toward advanced information and technology era. This research aims to find a practical solution on how to integrate trust during the design and development process of an e-commerce website. The research examines consumers trust and behavior by understanding the concept of trust, reviewing several trust related models, mechanisms and technologies proposed and recommended by other scholars. The research also proposed a model that shows how consumer trust is developed and communicated between two parties. It is found that there are six categories of trust mechanisms and technologies that web merchants can utilize in order to integrate trust in their website. It is also found that consumer characteristics have direct influenced on consumer purchasing intentions while web merchants should have trustworthiness characteristics such as ability, integrity and benevolence for consumer to evaluate and decide. This research provides guidelines for web merchants to understand more about consumer trust in order for them to build a secured and trusted e-commerce website.